A Modification of the Broström-Gould Procedure. Issue 1 (March 2015) - Molloy, Andy P.; Perera, Anthony; Guillo, Stephane
Abstract : Ankle lateral ligament injuries are one of the most common sporting injuries, with the majority being successfully treated conservatively. However, reconstruction may be required if this fails. In the majority of cases this will be an anatomic reconstruction, usually a variation of a Broström-Gould procedure. We present a new modification of anatomic repair with reinforcement by the extensor retinaculum and a periosteal flap with the use of a suture anchor in foot and ankle surgery. The steps of the modification are: (1) repair of the lateral structures to the distal fibula using 2 suture anchors; (2) reinforcement of fibula subperiosteal flap to prevent tearing during imbrications; and (3) repair of the subperiosteal flap to the lateral ligament complex and the inferior extensor retinaculum. The early results of our modification show it to be safe, successful, and comparable to previously published series with all patients having objectively and subjectively stable ankles at final follow-up. Further prospective evaluation is necessary for this promising technique. Level of Evidence: Diagnostic Level 5. See Instructions for Authors for a complete description of levels of evidence.